2019
DOI: 10.1002/ese3.550
|View full text |Cite
|
Sign up to set email alerts
|

Design and testing of highly transparent concentrator photovoltaic modules for efficient dual‐land‐use applications

Abstract: Two types of highly transparent concentrator photovoltaic (CPV) modules that separately utilize direct sunlight and diffuse sunlight for efficient dual‐land‐use applications were designed and tested. The type A module, comprising a typical‐scale CPV lens and solar cells, has a completely direct‐diffuse‐separated design for power generation and other solar applications. On the other hand, the type B module, consisting of a microscale CPV lens and solar cells, was designed to increase the amount of direct sunlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For example, although in this study, we used the less transparent TPU sheet because the electrode pattern can be easily formed by screen-printing, substituting highly transparent and stretchable materials (e.g., polydimethylsiloxane: PDMS) improves the module transmittance to the sunlight; consequently, unutilized sunlight for power generation can be transmitted under the module while generating the power comparable to the Si module. Therefore, also given the stretchability to be fitted to 3D curved surfaces with sharp curvature, this upgraded concept would be a promising technology for efficient dual-land use (i.e., semi-transparent CPV module [51][52][53] ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, although in this study, we used the less transparent TPU sheet because the electrode pattern can be easily formed by screen-printing, substituting highly transparent and stretchable materials (e.g., polydimethylsiloxane: PDMS) improves the module transmittance to the sunlight; consequently, unutilized sunlight for power generation can be transmitted under the module while generating the power comparable to the Si module. Therefore, also given the stretchability to be fitted to 3D curved surfaces with sharp curvature, this upgraded concept would be a promising technology for efficient dual-land use (i.e., semi-transparent CPV module [51][52][53] ).…”
Section: Discussionmentioning
confidence: 99%
“…They selectively transmit sunlight in a specific spectral range essential for plant growth, while also concentrating the remaining sunlight for power generation. Sato and Yamada [34] examined different types of CPV cells and found that they exhibit higher electricity yields compared to the partially transparent modules. However, even though these modules are more efficient, they are provided at a significantly higher cost, since manufacturer processes for mass production are yet to be implemented [35].…”
Section: Technological Advancesmentioning
confidence: 99%
“…Still, the decoupling loss and material attenuation become more significant, leading to a reduction in the system's efficiency [13]. That is why we chose the system length as 1 m; moreover, this size is also easy to compare with previously tested CPV systems [6]. After choosing the length of the flat waveguide, all parameters, such as the freeform lens array, the size of the prisms, and the length of the system, were fixed.…”
Section: System Designmentioning
confidence: 99%
“…However, the low density also reduces the amount of electricity produced. Sato and Yamada [6] designed and tested two types of highly transparent concentrator photovoltaic (CPV) modules for dual land use applications. The authors' system removed traditional PV cells' shade effect; however, the system is not suitable for locations with insufficient annual diffused sunlight for plant growth.…”
Section: Introductionmentioning
confidence: 99%